KONFLIK DALAM CERPEN ANAK-ANAK MAJALAH BOBO DAN IMPLEMENTASINYA DALAM PEMBELAJARAN APRESIASI PROSA FIKSI - Masyitah Maghfirah Nizam (IAIN MADURA, 2016)
An important element in an event that involves a character is a conflict. The event without a conflict makes the story uninteresting. The problems that become the focus of this study are the conflict in children’s short story in Bobo Magazine and its implementation in appreciational learning of fictional prose. The conflicts in children’s short story in Bobo Magazine can be classified into internal and external conflicts. The results of conflict analysis in children short story in Bobo Magazine can be implemented in learning of literature to the students of Elementary School/Islamic Elementary School. Through understanding the various conflicts in children's stories, students can manage themselves. Students are able to learn from mistakes made by the actors there without doing the same mistakes.